Aspek-Aspek Filosofi Kepemimpinan Dalam Al-Qur'an Dan As-Sunnah - Hafniati, Hafniati (AL-ADYAN, 2018)
Leadership is the ability of a person to influence and motivate others to do something according to common goals. Leaders must be based on the iman, ta'abbudi, charity sholeh and akhlaqul karimah in carrying out his leadership to achieve prosperity and salvation of the world and the hereafter. In the Qur'an and as-Sunnah are known several words of designation for leadership include: Khalifah, Amiir (ulul amr), and Imamah, region, and ri'ayah. A leader must have at least four aspects as Rasulullah SAW exemplifies, namely: Shiddiq, Amanah, Tabligh and Fathanah. Shiddiq means honest in word and deed, trust means trustworthy in keeping responsibility, Tabligh means convey all kindness to its people and fathanah means smart in managing society. The purpose of leadership in Islam is to uphold Islam (Iqamatuddin) and world based on Shari'a Islam